The Effectiveness o f Entomopathogenic Fungi Beauveria bassiana with the Addition of Insect Growth Regulator Lufenuron f or Controlling Bactrocera carambolae - Mochammad Syamsul Hadi; Toto Himawan; Luqman Qurata Aini (Journal of Tropical Life Science, 2013)
The study of the effectiveness of entomopathogenic fungus Beauveria bassiana (Bals) Vuill. with the addition of an insect growth regulator (IGR) lufenuron to control the fruit fly Bactrocera carambolae (Drew and Hancock) (Diptera: Tephritidae) was conducted at the Laboratory of Toxicology and Laboratory of Entomology, Department of Plant Pests and Diseases, Faculty of Agriculture, University of Brawijaya Malang from March 2012 until December 2012. This study examined the effect of lufe-nuron to the development and sporulation of B. bassiana and the effectiveness of the fungus B. bassiana in combination with several concentrations of lufenuron (0.5, 1, 1.5 mL/L) on the mortality of fruit fly larvaB. carambolae. The results showed that the addition of lufenuron at the concentration of 1 mL/L could significantly increase the sporulation of B. bassiana. The addition of B. bassiana at 108 spores/mL combined with lufenuron at the concentration of 1 mL/L applied to compost pupation medium of larva of B. carambolae is significantly able to suppress the formation of the fruit fly pupa and imago of B. carambolae